2011
DOI: 10.1121/1.3605534
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic analysis of a rectangular cavity with general impedance boundary conditions

Abstract: A Fourier series method is proposed for the acoustic analysis of a rectangular cavity with impedance boundary conditions arbitrarily specified on any of the walls. The sound pressure is expressed as the combination of a three-dimensional Fourier cosine series and six supplementary two-dimensional expansions introduced to ensure (accelerate) the uniform and absolute convergence (rate) of the series representation in the cavity including the boundary surfaces. The expansion coefficients are determined using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…This problem is mathematically related to the inability to converge of the traditional Fourier series on the boundaries of a domain under general boundary conditions. To overcome this difficulty, in this study, a 3-D version of an improved Fourier series representation previously developed for the in-plane vibrations of elastically restrained plates will be used to expand the sound pressure inside the cavity [9].…”
Section: Improved Fourier Series Representation Of Admissible Functionmentioning
confidence: 99%
“…This problem is mathematically related to the inability to converge of the traditional Fourier series on the boundaries of a domain under general boundary conditions. To overcome this difficulty, in this study, a 3-D version of an improved Fourier series representation previously developed for the in-plane vibrations of elastically restrained plates will be used to expand the sound pressure inside the cavity [9].…”
Section: Improved Fourier Series Representation Of Admissible Functionmentioning
confidence: 99%
“…There are numerous analytical works that demonstrated the influence of dissipative material on the walls of an enclosure [Bruneau et al, 1985;Du et al, 2011;Lanoye et al, 2008;Martin and Bodrero, 1997;Pan et al, 1999;Suzuki et al, 1989]. They showed that the interior noise of an enclosure can be reduced especially if the placement of sound absorption materials is optimized.…”
Section: Sound Absorption Materialsmentioning
confidence: 99%
“…Other than Thorsson's study [14], one can refer to works by Namba and Fukushige [15] and Selamet et al [16] who showed that coupling porous materials and resonators is efficient in the context of attenuation of sound propagation in ducts. A recent work by Du et al [17] proposed a model for studying the effect of non-uniform impedance boundary conditions on rectangular cavities and showed that decay times strongly vary depending on the distribution. Therefore, there is still a need to study non-uniform admittance profiles in the context of outdoor noise abatement systems.…”
Section: Introductionmentioning
confidence: 99%